ACADEMIC VOYEURISM: THE WHITE GAZE IN SOCIAL WORK - Murray-Lichtman, Andrea; Elkassem, Siham (Canadian Social Work Review / Revue canadienne de service social, 2021)
This article explores the insidiousness of racism and White supremacy embedded within the social work academy. We conceptualize the social work academy as the institutionalized practices within social work education, research, policy, and practice. As such, the social work academy is the bedrock that continues to perpetuate racism and colonialism within the profession. Anchored by an integrative analysis of social work that draws on both postcolonial and critical race theory, we theorize that, rooted in this foundation of oppression, White supremacy in social work often manifests as academic voyeurism—the non-performative White gaze. We suggest that academic voyeurism within the social work academy renders Black people, Indigenous people, and People of Colour (BIPOC) as bodies to be studied, exoticized, and theorized about, without any substantive anti-racist change or action required. Academic voyeurism sustains social work’s dissonant position—its endorsement of social justice alongside its simultaneous ambivalence towards racism and White supremacy. The discussion draws on historical underpinnings, research, and experiential data to turn the gaze onto the academy, illuminating the implications of academic voyeurism on racialized bodies and the social work profession’s broader goals. The discussion concludes with a call to collective action for racialized social workers and those wishing to be justice-seeking accomplices.